Bent polyynes: Ring geometry studied by Raman and IR spectroscopy - Lucotti, Andrea; Tommasini, Matteo; Chalifoux, Wesley A.; Fazzi, Daniele; Zerbi, Giuseppe; Tykwinski, Rik (Journal of Raman Spectroscopy, 2012)
Infrared (IR) and Raman spectroscopy have been used to examine the vibrational characteristics of a series of three macrocyclic tetraynes in comparison with an acyclic analog. By changing the length of the alkyl tether of the macrocycles, varying degrees of bending of the tetrayne moiety can be achieved, and the joint use of IR and Raman spectroscopies provides an avenue to probe the impact of bending on the sp-chain. The spectroscopic data show a general trend toward decreasing activation of Raman bands in the IR spectra, and vice versa, as bending of the polyyne chain is decreased. Density functional theory calculations provide a detailed rationalization of the experimental observations. Copyright © 2011 John Wiley & Sons, Ltd.